Analisis Kelayakan Pengembangan Usaha Rumah Makan Krebo Jantan - Dwiputra, Gerry Anugrah (Universitas Serang Raya, 2017)
At this time Krebo Jantan Restaurant has plans to conduct business development in the field of food. Krebo Jantan Restaurant has a problem as to whether its business development plan can provide feasibility for future growth of the company. The purpose of this study is to determine the possibility of the business plan for the development of food business with the limits of research on the assessment of financial aspects. Primary data collection is done through field observation, interview and questionnaire filling. Objects in interviews and surveys are business owners and residents around the place of business. Secondary data are obtained from literature studies. Data were analyzed by using Payback Period (PBP) method, Present Net Value (NPV) method, and Internal Rate of Return (IRR) Method. The result of the research shows the ability of the company to return all investment cost is for four years eight months. Cash funds collected from year to year if assessed at present with a positive value at the end of year 5 (five) and the ability of the company's business to provide annual average return/dividend amounted to 20.494%. Based on the results of financial analysis shows that all economic feasibility criteria are met so that the development of business feasible to be carried out under standard conditions,